Attenuation of energetic electrons and impact ionization in the ionosphere - Prasad R.Y.; Singh R.N. (My University, 2025)
Attenuation of energetic electrons in the energy range 1-300 keV precipitating in the ionosphere has been calculated and the resulting height profile in the range 50-300 km has been shown. The impact ionization produced by precipitating electrons of energy 3-300 keV has been calculated and its height profile is shown. It is seen that impact ionization increases with increasing energy of precipitating electrons. High energy electrons penetrate deeper into the ionosphere and produce high degree of ionization. © 1970.